Online hate speeches as threats to peace and deteriorations of unity and harmony intra-religion in the Ethiopian Orthodox Tewahedo Church (EOTC) - Geremew Chala (Cogent Social Sciences)
This study examined how online hate discourses following the attempts of regional parish administration in Oromia and Tigray regions have deteriorated peace, unity and harmony among Tewahedo Church (EOTC) Christians. The growth of hate speech, which is connected to religious undertones and also contributed to racial and political differences has tamped down the new digital platform. To examine users’ comments gathered from the Facebook pages and YouTube channels of EOTC TV, Oromia and Nations Nationality Synod (ONNS) and Omega TV, the study used a qualitative conceptual content analysis research design. Using the social media analysis, it was discovered that there is a substantial occurrence of hate speech on social media that poses a threat to peace and degrades unity and harmony within the EOTC. Hatred tendencies going towards and going against the three organisations’ social media networks were identified. Neutral comments were also dealt with as they were important in strengthening unity and harmony within the church. Most of the hate speeches were amplifying existing disagreements and divisions within the EOTC. The results of the study indicate that different factions or groups used some social media platforms to spread their narratives, demonise opposing viewpoints, and further polarise the community. The religious fathers need to address the concerns about the schism and its potential consequences on the EOTC’s reputation, followers, and religious practices to minimise the spread of hate speech.